OUTCOME OF RUBBER BAND LIGATION OF HAEMORRHOIDS USING SUCTION LIGATOR - Khaliq, Tanwir; Shah, S. Aslam; Mehboob, Ansar (Journal of Ayub Medical College Abbottabad, 2004)
Background: Haemorrhoids are a common surgical problem seen in the outpatient department. Rubber band ligation using suction is an effective treatment for symptomatic haemorrhoids but associated with significant morbidity.This prospective observational study was carried out to assess the efficacy, effectiveness and complications of rubber band ligation performed in outpatient for symptomatic haemorhoids using suction ligator. The results and outcome of procedure performed by the consultants and senior residents were also compared. Methods: 56 consecutive patients with symptomatic haemorrhoids underwent rubber band ligation in the outpatient clinic of the department of general surgery, Pakistan Institute of Medical Sciences. Outcome measures were symptomatic cure i.e. stoppage of bleeding and reduced mucosal prolapse. Complications were categorized as immediate, early (within one week) and late (within 3 months). Results: Symptomatic cure was achieved in 50(89.20%) patients (stoppage of bleeding and reduced mucosal prolapse). Six (10.72%) patients required further banding. Pain (mild to severe) was most common immediate and intermediate complication (14 and 20 patient's respectively). Conclusion: Rubber band ligation is an effective, outdoor procedure for symptomatic haemorrhoids, but associated with certain degree of morbidity. Keywords: Hemorrhoids, Suction Ligator, Banding.